2022
DOI: 10.1038/s41598-022-19914-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of artificial intelligence for automated measurement of cervical lordosis on lateral radiographs

Abstract: Cervical sagittal alignment is an essential parameter for the evaluation of spine disorders. Manual measurement is time-consuming and burdensome to measurers. Artificial intelligence (AI) in the form of convolutional neural networks has begun to be used to measure x-rays. This study aimed to develop AI for automated measurement of lordosis on lateral cervical x-rays. We included 4546 cervical x-rays from 1674 patients. For all x-rays, the caudal endplates of C2 and C7 were labeled based on consensus among well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The ICC values were above 0.90 for C2-7 SVA, C2S, C27L, and L1I, indicating excellent agreement between the AI-based measurements and those obtained by specialists. Our study found an mean error of 3.625 for C2-7L measurements, which is comparable to the mean error of 3.3 for cervical lordosis obtained from an AI model trained on 4546 cervical X-rays [17]. The relatively high error may be attributed to including patients with deformities, those with poorly visible C7 endplates due to obesity, and patients with short necks who may have a different shoulder girdle position in the training process.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The ICC values were above 0.90 for C2-7 SVA, C2S, C27L, and L1I, indicating excellent agreement between the AI-based measurements and those obtained by specialists. Our study found an mean error of 3.625 for C2-7L measurements, which is comparable to the mean error of 3.3 for cervical lordosis obtained from an AI model trained on 4546 cervical X-rays [17]. The relatively high error may be attributed to including patients with deformities, those with poorly visible C7 endplates due to obesity, and patients with short necks who may have a different shoulder girdle position in the training process.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to previous studies, our research utilized over 900 images for training, resulting in an average error of 8.789 • for Lumbar Lordosis Angle (LLA) measurements. Another study that trained on 629 individuals for LLA measurements showed a similar level of mean error at 8.055 • [17]. Our model also demonstrated lower error compared to a model trained on 493 individuals using EOS, which reported a mean absolute error (MAE) of 11.5 • [18].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…While analyses based on single image features have produced satisfactory outcomes as evidenced by studies such as Jebri’s [ 27 ] use of a machine learning-based random forest classifier model for detecting intervertebral space narrowing and osteophyte formation, Tamai’s [ 28 ] segmentation of cervical ligament calcification using the EfficientNet-B2 model, Fujimori’s [ 29 ] application of the EfficientNet-B4 model to identify cervical lordosis, and Chen’s [ 30 ] diagnosis of cervical spine scoliosis using the ResNet model. These contributions notwithstanding, CS cannot be adequately represented by single image features alone but rather as a constellation of multiple imaging features.…”
Section: Discussionmentioning
confidence: 99%